Mycoplasma penetrans methionyl-tRNA synthetase dimerizes via tandem N-terminal ancillary domains - Behrouz Ghazi Esfahani; Madelynn K. Bowman; Nidhi Walia; Rebecca W. Alexander; M. Elizabeth Stroupe (PLoS ONE, 2026)
Diverse aminoacyl-tRNA synthetase gene fusions are now recognized as a common mechanism for enhancing genetic diversity across all domains of life. The metS gene from Mycoplasma penetrans is a striking example of such an evolutionary mechanism because although M. penetrans has a condensed genome, the metS gene is nearly twice the size of a typical bacterial gene encoding methionyl-tRNA synthetase (MetRS). We used cryo-EM to analyze the structure of the metS gene product (MpMetRS) to show that it is the fusion of three distinct enzyme domains: an N-terminal domain of unknown function, a dimeric alanine-glyoxylate aminotransferase (AGAT), and a MetRS. Only the first two N-terminal domains show two-fold symmetry and were resolved to 3.27 Å resolution; the MetRS domain is only partially resolved to 3.66 Å resolution. Modelling the full structure shows that a rotation of the MetRS domain relative to the AGAT domain must occur to accommodate a tRNA-bound MetRS. Further rearrangement of the catalytic domains would also be necessary to bring the active sites adjacent to one another if this unique assembly of catalytic domains functions to channel substrates to MetRS.